Measurements of 14CH4 and 14CO in ice from Taylor Glacier: Last Deglaciation and Deep Core Results - Petrenko, Vasilii (IEDA: US Antarctic Program Data Center, 2018)
Abstract: This data set contains measurements of 14CH4 and 14CO in ice cores from Taylor Glacier, Antarctica. This includes measurements in ice from the last deglaciation (18 - 8 kyr), for the purposes of paleoatmospheric 14CH4 reconstruction. The data set also includes measurements in older ice (50 - 70 kyr) from a deep ice core, made for the purposes of studying in situ cosmogenic 14C production in ice. All data are in excel format.